(untitled) (Physical Education, Health and Social Sciences, 2025)
To examine the presence and strength of a relationship between managerial coaching capability and team performance. To identify moderating and mediating contextual factors within this relationship. Based on past explorations, this present research focuses on identifying how some elements of managerial training and development practice in terms of coaching behaviors in leadership and ways of allocating resources to teams affects team efficiency and success. For this research the data was gathered conveniently and the respondents were mostly students from a University. Furthermore, survey links were spread the WhatsApp application and through QR codes. The data was analyzed using Statistical Package for Social Sciences (SPSS) software, and the various tools ranging from Confirmatory Factor Analysis, Model Fitness Index and Linear Regression hypothesis test were used. The study outcomes show a strong, positive relationship between managerial coaching behaviors, prospecting, questioning, positive feedback, and direction and team performance measures utilizing task performance, work motivation, and learning. Thus, the study highlights the need to fill these gaps and examine contextual antecedents of managerial coaching skills and team performance. This way organizations can enhance advance on the coaching solutions